Food, fizzy, and football: promoting unhealthy food and beverages through sport - a New Zealand case study - Carter Mary-Ann; Signal Louise; Edwards Richard; Hoek Janet; Maher Anthony (BMC, 2013)
Abstract Background High participation rates in sport and increasing recognition of how diet benefits athletic performance suggest sports settings may be ideal locations for promoting healthy eating. While research has demonstrated the effect of tobacco and alcohol sponsorship on consumption, particularly among youth, few studies have examined the extent or impact of food and beverage company sponsorship in sport. Studies using brand logos as a measure suggest unhealthy foods and beverages dominate sports sponsorship. However, as marketing goes beyond the use of brand livery, research examining how marketers support sponsorships that create brand associations encouraging consumer purchase is also required. This study aimed to identify the characteristics and extent of sponsorships and associated marketing by food and non-alcoholic beverage brands and companies through a case study of New Zealand sport. Methods We conducted a systematic review of 308 websites of national and regional New Zealand sporting organisations to identify food and beverage sponsors, which were then classified as healthy or unhealthy using nutrient criteria for energy, fat, sodium and fibre levels. We interviewed 18 key informants from national and regional sporting organisations about sponsorships. Results Food and beverage sponsorship of sport is not extensive in New Zealand. However, both healthy and unhealthy brands and companies do sponsor sport. Relatively few support their sponsorships with additional marketing. Interviews revealed that although many sports organisations felt concerned about associating themselves with unhealthy foods or beverages, others considered sponsorship income more important. Conclusions While there is limited food and beverage sponsorship of New Zealand sport, unhealthy food and beverage brands and companies do sponsor sport. The few that use additional marketing activities create repeat exposure for their brands, many of which target children. The findings suggest policies that restrict sponsorship of sports by unhealthy food and beverage manufacturers may help limit children's exposure to unhealthy food marketing within New Zealand sports settings. Given the global nature of the food industry, the findings of this New Zealand case study may be relevant elsewhere.